Quantum Field Theory and Beyond : Essays in Honor of Wolfhart Zimmermann : Proceedings of the Symposium in Honor of Wolfhart Zimmermann's 80th Birthday, Ringberg Castle, Tegernsee, Germany, 3-6 February 2008 - Zimmermann, Wolfhart; Seiler, Erhard, 1942-; Sibold, K. (Klaus) (World Scientific, 2008)
This book contains a collection of essays written in honor of Wolfhart Zimmermann's 80th birthday, most of them based on talks presented at a symposium in his honor. The book shows the unifying force of a subject (Quantum Field Theory) and a person (Zimmermann). It ranges from fundamental questions in quantum physics over applications to particle physics and noncommutative geometry to the latest developments in many body theory and dynamical systems. These key ideas are elucidated by worldwide-recognized experts including Faddeev, Becchi, Buchholz, Lowenstein and Salmhofer. Readers seeking examples on how a subject has evolved, diversified and deepened over the course of several decades and how a single person can influence this process can find here a perfect illustration. Altogether, readers are treated to a high-brow intellectual adventure.